Effect of Physical Exercise on College Students’ Life Satisfaction: Mediating Role of Competence and Relatedness Needs - Zhang, Yunqi; Ren, Menghao; Zou, Shengqi (Frontiers in Psychology, 2022)
This study examined the effect of physical exercise on the life satisfaction among college students. On the basis of the Basic Psychological Need Theory, the mediating roles of competence and relatedness needs satisfaction and their differences among college students in physical education (PE) majors and non-PE majors were explored. The sample included 1,012 college students who were selected to participate in an online survey. Major findings were as follows: (1) The total effect of physical exercise commitment on college students’ life satisfaction was marginally significant while that of physical exercise adherence was not significant; (2) The effect of physical exercise commitment was observed exclusively through the mediating role of relatedness need satisfaction, while that of physical exercise adherence was through both competence and relatedness needs satisfaction; (3) In terms of differences caused by major, only one mediation path, that was, physical exercise → competence need satisfaction → college students’s life satisfaction was significant among PE majors. This study thus enriched the empirical research on the benefits of physical exercise to individual mental health, highlighted the particularity of college students majoring in PE, and provided targeted and sensible suggestions for the design of physical exercise intervention programs.